PEDAGOGICAL CHANGE IN THE AI ERA: INDONESIAN EFL TEACHERS' VOICES AND CONTEXTUAL CONSTRAINT - Rahmiati, Rahmiati; Al Tasa, Fiza Rauzika; Sanjaya, Muhammad Arif; Zulida, Evi; Hasrina, Noliza; Isda, Irma Dewi; Chairuddin, Chairuddin (Universitas Islam Sumatera Utara (UISU), 2025)
This study examines how Indonesian English as Foreign Language (EFL) teachers perceive and negotiate pedagogical change arising from the integration of Artificial Intelligence (AI) into language instruction. This research uses an interpretive qualitative approach through semi-structured interviews with seven teachers from diverse institutional backgrounds in Sumatera. Thematic analysis identified six key themes: (1) pedagogical change through AI integration, (2) evolving teacher identity, (3) reflective professional agency, (4) contextual constraints, (5) students' engagement and critical awareness, and (6) the need for instructional support and teacher training. Findings indicate that AI tools, such as ChatGPT and Grammarly, have facilitated a shift toward more student-centered, project-based, and reflective teaching practices. Teachers reported a redefinition of their roles from content transmitters to facilitators and mentors, with an increasing emphasis on assessing learning processes rather than outcomes. However, AI integration was hindered by infrastructural limitations, unequal access to technology, and a lack of AI literacy. The study reveals that technological transformation in ELT is not merely technical but also shaped by contextual realities and teacher identity. It highlights the need for context-sensitive professional development and inclusive policy support that enhance teachers' adaptive capacities in an AI-mediated learning environment.